FORMATION OF PSYCHOTHERAPEUTIC POSITION FUTURE TEACHER IN THE STUDY PROCESS PSYCHOLOGICAL AND PEDAGOGICAL DISCIPLINES (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the substance, potentialities and the experience of formation of psychotherapeutic position of the future teachers in the process of psychological-pedagogical subjects learning.